PENERAPAN DEEP BREATHING EXERCISE DAN TERAPI MUSIK RELIGI TERHADAP TEKANAN DARAH PASIEN HIPERTENSI PADA LANSIA - Luluk Cahyanti (Pusat riset dan Inovasi Nasional, 2022)
A common disease experienced by the elderly is hypertension. Cases of hypertension in Demak are quite high, one of them is in Mranggen village. This reality proves that many people still ignore hypertension. Because there are sufferers who feel no symptoms and there are symptoms such as headaches, weakness, fatigue, shortness of breath and blurred vision. If not treated immediately it will cause complications such as kidney failure, stroke, coronary heart disease and retinopathy. It is of course important to make efforts to control blood pressure. A combination of non-pharmacological management of deep breathing exercise and religious music is one of the efforts that can be made. The purpose of this study was to describe the administration of a combination of deep breathing exercise and religious music therapy to the blood pressure of elderly hypertensive patients. This research uses descriptive case study research with a nursing care process approach.The number of samples is 2 respondents, with the criteria of elderly clients who have hypertension, clients who do not take medication during hypertension in order to determine the effectiveness of the action, clients who can communicate well, and clients who are willing to be respondents. Deep breathing exercises and religious music are carried out once a day for 3 days in 1 week with a duration of 15 minutes. Blood pressure measurement using a sphygmomanometer and stethoscope. Blood pressure measurements were taken before and after the procedure. The results showed that the blood pressure of respondent 1 before and after being given deep breathing exercise therapy and religious music for 3 consecutive days with a duration of 15 minutes, the blood pressure on the first day before receiving therapy was 160/70 mmHg and after being given therapy for 3 days on the last day the blood pressure became 150/60 mm Hg. In respondent 2 before and after being given deep breathing exercise therapy and religious music for 3 consecutive days with a duration of 15 minutes the blood pressure on the first day before receiving therapy was 179/80 mmHg and after being given therapy for 3 days on the last day the blood pressure was 156/70 mmHg .